Navigating environmental attitudes - Heberlein, Thomas A., 1945- (New York ; Oxford : Oxford University Press, 2012)
Solving environmental problems requires a scientific understanding of public attitudes. Bringing together theory and practice, 'Navigating Environmental Attitudes' provides a realistic understanding of why and how attitudes matter when it comes to environmental problems; and how, by balancing natural with social science, we can step back from false assumptions and unproductive, frustrating programs to work toward fostering successful, effective environmental action.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Environmental management -- Psychological aspects; Environmental sciences -- Psychological aspects; Environmental sociology; Environmental psychology